The relationship between trait emotional intelligence and career success - Pregnolato, Aurélia (2015)
In order to consider the contribution of emotional intelligence (EI) to career success (CS), this research analysed the relationship between Trait EI (TEI) and career success. The study covered a sample of 154 banking managers across the European Union. Correlation analyses indicated a strong relationship (Pearson’s r .759) between banking manager’s trait EI level and career success. Results from regression analyses showed that TEI, and especially its dimension emotionality have incremental validity in predicting career success (β=0.368), then sociability (β=0.225), Self-control (β=0.184) and Well-being (β=0.014) are respectively in the next rating. Demographic characteristics were also analysed in order to determine whether or not it might affect TEI and CS in this research. Demographic variables expressed weak predicting power on TEI (R a =,037) and CS (R a =,056). Findings of this research provide support to the banking industry in the use of trait emotional intelligence measures as predictors of managers’ career success.